2008
DOI: 10.1016/j.exer.2007.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of retinal degeneration in the absence of alpha crystallins in an in vivo model of chemically induced hypoxia

Abstract: This study evaluated the role of crystallins in retinal degeneration induced by chemical hypoxia. Wild type, αA-crystallin (−/−), and αB-crystallin (−/−) mice received intravitreal injection of 12 nmol (low dose), 33 nmol (intermediate dose) or 60 nmol (high dose) cobalt chloride (CoCl 2 ). Hematoxylin and eosin and TdT-mediated dUTP nick-end labeling (TUNEL) stains were performed after 24 hours, 96 hours, and 1 week post-injection, while immunofluorescent stains for αA-and αB-crystallin were performed 1 week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 47 publications
5
74
0
1
Order By: Relevance
“…[3][4][5]9,10,[26][27][28][29][30] Overexpression of aB- crystallin was found to offer protection while silencing rendered cells susceptible to apoptosis from oxidative injury. Signaling mechanisms of cellular protection varied depending on the imposed stress stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5]9,10,[26][27][28][29][30] Overexpression of aB- crystallin was found to offer protection while silencing rendered cells susceptible to apoptosis from oxidative injury. Signaling mechanisms of cellular protection varied depending on the imposed stress stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…2 Both a-crystallins are expressed in RPE cells and in the retina; higher expression of aBcrystallin was found in the RPE while aA-crystallin was found mostly in photoreceptors and astroglial and Müller cells. 3,4 Furthermore, aB-crystallin was shown to be upregulated with several stress stimuli and to translocate to nuclei and mitochondrial compartments of RPE cells. 3,5 Microarray and proteomic analysis and histological studies have revealed that a-crystallin accumulates in drusen.…”
mentioning
confidence: 99%
“…α-crystallins are major proteins of the small heat shock protein family and are expressed in several tissues [66][67][68] . α-crystallins have been studied extensively in the lens for their chaperone function, but α-crystallins are now generally understood to have additional non-lens roles [18][19][20][21]69,70] . In addition to being a molecular chaperone, α-crystallin functions in cell death inhibition, neuroprotection, proteosomal interactions, and regulation of angiogenesis [18][19][20][21]70,71] .…”
Section: Interaction Of Msra With Other Proteinsmentioning
confidence: 99%
“…To counteract ROS damage, organisms have evolved multiple defense systems, including low molecular weight compounds and antioxidant enzymes that protect against oxidative stress. The antioxidant system includes glutathione peroxidase [6,7] , superoxide dismutase [8,9] , catalase [10,11] , thioredoxin reductase (TR) [12] , methionine sulfoxide reductase (Msr) [13][14][15][16][17] and several other proteins, including but not limited to small heat shock proteins, particularly α-crystallins [18][19][20][21] . Msrs are prominent among these antioxidant enzymes because of their roles as repair enzymes and indirect scavengers of ROS [4,22] .…”
Section: Introductionmentioning
confidence: 99%
“…12 An increase of a-crystallin expression is a normal response to stressors. [27][28][29] At the same time, chronic stress can downregulate aB-crystallin, and this change could promote degenerative # Significant differences between untreated OXYS and Wistar rats (P < 0.05); *a significant effect of treatment with SkQ1 (P < 0.05). Confocal immunofluorescent images depict aB-crystallin (red signal) detected within the retina and RPE in OXYS rats (C) compared to disease-free Wistar (D) rats and (E) SkQ1-treated OXYS rats (250 nmol/kg per day from 1.5 to 4 months of age).…”
Section: Discussionmentioning
confidence: 99%